2009
DOI: 10.4161/cbt.8.1.7204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of renal cancer cell growth by oncolytic adenovirus armed short hairpin RNA targeting hTERT gene

Abstract: RNA interference (RNAi) has been proved to be a powerful tool for gene knockdown purpose and holds a great promise for the treatment of cancer. Our previous study demonstrated that the reduction of hTERT expression by means of chemically synthesized siRNAs and shRNAs expressed from plasmid resulted in proliferation inhibition in human renal carcinoma cells. In this study, we constructed a novel oncolytic adenovirus-based shRNA expression system, ZD55-hTERT, and to explore ZD55-hTERT-mediated RNAi for hTERT gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Recently, Zheng et al [59,60] focused on several constructs using an oncolytic virus to carry siRNA. Examples include a siRNA against Ki67, and a siRNA against human telomerase reverse transcriptase (hTERT), which acts as an antiproliferative and apoptosis inducer in cancer cells.…”
Section: Tmz In Combination With Mgmt Inhibitors: An Effective Cancermentioning
confidence: 99%
“…Recently, Zheng et al [59,60] focused on several constructs using an oncolytic virus to carry siRNA. Examples include a siRNA against Ki67, and a siRNA against human telomerase reverse transcriptase (hTERT), which acts as an antiproliferative and apoptosis inducer in cancer cells.…”
Section: Tmz In Combination With Mgmt Inhibitors: An Effective Cancermentioning
confidence: 99%
“…ZD55, an E1B 55 kDa-deficient oncolytic adenovirus that is similar to ONYX-015 was constructed by Liu [84]. His collaborator Chu constructed ZD55-siApollon, ZD55 containing the U6 promoter to express shRNA directed against Apollon, a membrane-associated inhibitor of apoptosis protein [58].…”
Section: Oncolytic Adenovirus-mediated Rna Interference For Cancer Thmentioning
confidence: 99%
“…Comparing the antitumor activity of ZD55, ZD55 expressing Ki67 shRNA (ZD55-Ki67) and a non-replicating adenoviral vectors expressing Ki67 shRNA (AD-Ki67), we found ZD55-Ki67 had more potent antitumor effects both in vitro and in vivo. In another study [84], we constructed a ZD55-based shRNA expression system targeting human telomerase reverse transcriptase (hTERT), ZD55-hTERT, to explore its hTERT gene silencing and antitumor outcomes. The study revealed that ZD55-hTERT could induce silencing of the hTERT gene, and is effective in suppressing telomerase activity, and inducing the apoptosis of tumor cells in vitro and in nude mice.…”
Section: Oncolytic Adenovirus-mediated Rna Interference For Cancer Thmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Like ONYX-015, ZD55 is defective in the E1B gene. The authors compared the antitumor activity of ZD55 expressing GFP (ZD55-EGFP), ZD55 expressing hTERT shRNA (ZD55-hTERT), and a conventional E1-deleted adenovector expressing hTERT shRNA (AD-hTERT) and found that compared with ZD55-EGFP or AD-hTERT, ZD55-hTERT had more potent antitumor effects, both in vitro and in vivo.…”
mentioning
confidence: 99%